2019
DOI: 10.1007/s40948-019-00104-5
|View full text |Cite
|
Sign up to set email alerts
|

Strength properties of fresh and weathered rocks subjected to wetting–drying cycles

Abstract: Unlike previous research on soft and clay-bearing rocks, this study seeks to investigate the effect of wetting and drying (W-D) cycles on the engineering properties of two hard rocks. A series of W-D cycles were applied to fresh specimens of greywacke and basalt, and their strength, slake durability and density were progressively assessed as the number of cycles increased. It was found that unlike the basalt, the strength of greywacke rapidly decreased with increasing W-D cycles while the rock density and slak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Clay-bearing rock strengths depend strongly on the weathering processes such as heating and cooling, wetting and drying, and freezing and thawing cycles [9][10][11]. A direct effect of moisture on such materials is the reduction in toughness due to particle swelling [12,13]. Saturated clay-bearing rocks were reported to have a compressive strength and elastic modulus up to about 90% of oven-dried counterparts [14].…”
Section: Introductionmentioning
confidence: 99%
“…Clay-bearing rock strengths depend strongly on the weathering processes such as heating and cooling, wetting and drying, and freezing and thawing cycles [9][10][11]. A direct effect of moisture on such materials is the reduction in toughness due to particle swelling [12,13]. Saturated clay-bearing rocks were reported to have a compressive strength and elastic modulus up to about 90% of oven-dried counterparts [14].…”
Section: Introductionmentioning
confidence: 99%
“…The spacing between the joints for each joint set necessary to determine block volumes was determined using the Cloud Compare Distances tool, with which the distances in different cliff face zones were measured and analyzed. Although some developed remote sensing methods that have been successfully applied to identify other discontinuity features (separation, infilling, discontinuity wall roughness, and weathering grade) [83,86,[93][94][95][96][97] were used in the remote sensing survey of the Raspadalica Cliff, it was found that the resulting data had too much scatter and were not as reliable as the data obtained by in situ traditional geological and geotechnical surveys. Based on the statistical analyses of the data obtained from the 3D HRPC model of Raspadalica Cliff using the Cloud Compare software, the mean values of the orientations, discontinuity sets spacing and persistence for the total area of the Raspadalica Cliff are presented in Table 2.…”
Section: Results Of the Geological And Geotechnical Surveymentioning
confidence: 99%
“…At Kaikōura, the role of repeated wetting and drying is important because of the prevalence of mudstone, which is vulnerable to clay mineral disaggregation, microcracking, and a reduction of material strength (Dick & Shakoor, 1992; Gratchev et al, 2019; Hall & Hall, 1996; Wong et al, 2016; Yang et al, 2019). Within the intertidal zone, the platform surface is susceptible to wave action to pluck or wear away at the weakened material.…”
Section: Discussionmentioning
confidence: 99%
“…The most potent erosion agent is water, which controls mechanical and chemical weathering processes, as well as enhancing erosion through wetting and drying cycles (Hall & Hall, 1996). The loading and unloading of water associated with absorption and desorption can reduce rock strength, making it more vulnerable to denudation (Gökçeoglu et al, 2000; Gratchev et al, 2019).…”
Section: Introductionmentioning
confidence: 99%